When Dorian meets Holmes: An interview with Scott Handcock. Issue 1 (1st April 2015) - Ue, Tom
Completed shortly after the first series, this interview with Scott Handcock explores his creative process with The Confessions of Dorian Gray (2012-present), an ongoing audio-play series for the British company Big Finish Productions. Handcock, a writer, producer, and director based in Cardiff, has worked on Doctor Who for both AudioGo and Big Finish, and Bernice Summerfield (1998-present), Gallifrey (2004-present), and Dark Shadows (2006-present). Dorian Gray stars Alexander Vlahos as its titular character. In 2014, Handcock's full-cast dramatization of Frankenstein, adapted by Jonathan Barnes, stars Arthur Darvill as Victor Frankenstein and Nicholas Briggs as the Creature. In this interview, we examine Handcock's views about horror, and how our understandings of Wilde's character and horror change as his story is set in different times and spaces.